Pomen poznavanja nacionalnega značaja in kulturnih posebnosti za slovensko gospodarsko diplomacijo - Rašković, Matevž (Teorija in praksa, 2011)
Despite growing interest in the study of culture and its dimensions in international business and international relations literature over the last few decades, most analyses neglect the issue of national character and its impact on international economic relationships. The concept of national character has emerged from the anthropology and social psychology literature. We believe the increased importance and interest in business diplomacy within the framework of international relations can gain substantially by addressing the issue and by analysing the concept of national character because this helps in anticipating the behavioural responses of foreign "partners" within the myriad communication and negotiation elements of diplomatic relationships. The purpose of this paper is to fill in the gap related to the exclusion of the concept of national character in the Slovenian (business) diplomacy literature, and to define and operationalise the concept of national character in terms of its usefulness for diplomatic practice. The basic goal of the paper is to show via the example of ex-Yugoslav countries (Slovenia, Croatia and Serbia) the most important elements of their national characters, addressing both their universality and contingency. We confirm the hypothesis that these selected ex-Yugoslav countries are by no means culturally heterogeneous through our comparisons, and further conclude with a series of recommendations and the implications these differences hold for the functioning of Slovenian business diplomacy in these selected countries.
Keywords: Narodni značaj; National character; Gospodarstvo; Economy; Diplomacija; Diplomacy; Slovenia; Slovenija; Croatia; Hrvaška; Serbia; Srbija; gospodarska diplomacija